Study on the influencing factors and intervention strategies of public panic buying during public health emergencies - Heting Wu; Ruirui Xie; Lili Ding; Huiling Dong; Guifang Ren (BMC Public Health)
Abstract Objective To examine the prevalence and influencing factors of panic buying of emergency supplies among the public during the coronavirus disease 2019 (COVID-19) epidemic and provide a reference for public responses. Methods Using a self-designed questionnaire on panic buying during COVID-19, we conducted an online voluntary anonymous survey among adult internet users (≥ 18 years) in China from June to July 2022. Descriptive analysis, χ 2 test and logistic regression analysis were used to explore the influencing factors of public panic buying. Results The high-risk categories for panic buying included younger individuals, women, students, and those with lower economic status (P < 0.05). Media factors, psychological panic, reference group, psychological value expectation, group identification, and social control ability were identified as important factors influencing the occurrence of public panic buying (P < 0.05). Among those factors, media influence, psychological panic, reference groups, psychological value expectations, and group identity increased the influence on panic buying, however, social control ability decreased the influence on panic buying. Conclusions Public panic buying behavior can have a negative impact on social stability, and it is crucial to reduce the occurrence of such behavior. Based on the empirical results of this study, we can propose intervention measures from several aspects, including media factors, psychological panic, reference group, psychological value expectation, group identification, and social control ability. However, this study only examined the risk factors influencing panic buying behavior. Future research could further analyze the pathways of influence among these factors.